'Fungal spondylodiscitis in a non-immunocompromised patient'. (9th March 2012) - Jorge, Vanda Cristina; Cardoso, Catarina; Noronha, Carla; Simões, José; Riso, Nuno; Vaz Riscado, Manuel
Abstract : Spondylodiscitis is an inflammatory disease, usually infectious, of one or more vertebral bodies and of corresponding intervertebral discs. The fungal aetiology is rare (less than 5% of cases), affecting mostly immunocompromised individuals. It is often a delayed diagnosis by the indolence of symptoms, presenting itself as a serious infection, which may result in important functional consequences. The authors present the case of a 75-year-old male, with constitutional complaints and intense back pain. Prior recent history of left hemicolectomy due to diverticulitis with multiple surgical complications, resulted in prolonged intensive care unit hospitalisation, and, later on, an episode of fungal endophthalmitis. The diagnosis of spondylodiscitis L5/S1 was performed by MRI. The patient underwent surgical disco-vertebral debridement and isolation of a Candida albicans was seen in the collected surgical material. No evidence of an immunossupressive status was found. Treatment was complemented with liposomal amphotericin B in the maximum recommended dose.